In Vitro Biocompatibility of Nanostructured Endodontic Materials Using SCAP Cells - Ćetenović Bojana; Čolović Božana; Vasilijić Saša; Pašalić Snežana; Jokanović Vukoman; Marković Dejan (Balkan Stomatological Society, 2017)
Background/Aim: Lately, fully innovative sol-gel method with high-temperature self-propagating reaction was used for the synthesis of new nanostructured endodontic materials, in combination with different radiopacifiers: bismuth (ALBO-MPCA1) and barium (ALBO-MPCA2). The aim of this study was to investigate the biocompatibility of nanostructured endodontic materials based on highly active calcium silicates and mixed with different radiopacifiers in comparison to MTA+ using human stem cells from the apical papilla- SCAP cells. Material and Methods: Morphology of the samples was studied by SEM. The tested materials were mixed with distilled water in a ratio 2:1 (m/m). Fifteen minutes fter the preparation, samples were used in the experiment. The biocompatibility of fresh materials, after 3h and 7 days, was tested using 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide- MTT test. Results: Samples mostly consisted of spherical and rode-like. The relative viability of cells increased following the exposure time. Conclusion: The biocompatibility of synthesized materials is comparable to the control material MTA+, and therefore these materials can be recommended for for further clinical stuadies.